PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 015 SEREMBAN JAYA KECAMATAN RIMBA MELINTANG - Suriyati '; Lazim,N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This Research is executed by because result learn the IPA expected by not yet reached the KKM specified by school namely 70. For that require to be done/conducted by a research with an eye to improve the result learn the IPA of student of class of V SD Country 015 Seremban Jaya of Kecamatan Rimba Melintang. School Year 2015 / 2016 by applying model the study of co-operative of type TSTS executed at April month;moon until May. Subjek in this research is student of class of V SD Country 015 Seremban Jaya with the amount 24 student, 10 joe and 14 women. this Desain Research is Research of Class Action ( PTK). Pursuant to result analyse the data indicate that the result learn to experience of the improvement. At elementary score of mean assess 60,83 completely is klasikal 29,17% ( is not complete), mounting at cycle of I mean assess is 73,13 completely is klasikal 62,50% ( is not complete) and cycle II namely 86,04 completely is klasikal 87,50% (Complete). Hereinafter of at activity learn and student also experience of improvement. Activity percentage learn at cycle of I meeting 1 that is 62,50% with the category enough, meeting 2 that is 70,83% good category while at cycle of II meeting 1 that is 87,50% with the good category very and meeting 2 namely 95,83% category very goodness. percentage of student Activity of at cycle of I meeting 1 that is 54,17% category enough, meeting 2 namely 66,67% category good while at cycle of II meeting 1 that is 79,17% with the good category and meeting 2 namely 83,33% category very is good. Than inferential research result that with the applying model the study of co-operative of type TSTS can improve the result learn the IPA of student of class of V SD Country 015 Seremban Jaya Kecamatan Rimba Melintang.Keyword : Model the pembelajan of co-operative of type TSTS, result of learning IPA